Analysis of Ecotourism Management Kampung Blekok in Situbondo, East Java - Saifana Iluj'Dhia Hakiki; Satti Wagistina (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
Kampung Blekok, as a one tourism destination in Situbondo Regency, has an attraction mangrove ecosystem and blekok birds. Adopt the concept of ecotourism makes this site necessary to pay attention for aspects of the natural environment, the social economy of the community, and education for tourists. This research purpose to determine the management capability by analyzing the Pressure State Response model. This research uses a quantitative approach with survey research methods. Based on the result of the analysis, it shows that the average score is 42,3% with not good. The low management capacity has as impact on the low interest of tourist returning to Kampung Blekok. Therefore it is important to optimize the availability of facilities and infrastructure, facilities, educating the local community about the importance of being environmentally conscious, as well as tourism management.